Metal Complexes of Schiff Base Derived from Terephthalaldehyde and 2-Amino-5-Ethyl-1,3,4-Thiadiazole Synthesis, Spectral and Thermal Characterization - Turan, Nevin; Sekerci, Memet (Taylor & Francis Inc, 2009)
The present study deals with the preparation of Schiff base and its chelates with some transition metal ions, e.g., Co(II), Ni(II), Cu(II) and Fe(II). The structures of the ligand N-(5-ethyl-1,3,4-thiadiazole-2-yl)terephthalaldehyde imine (L) and its complexes have been synthesized and characterized by IR, 1H-NMR spectra, elemental analyses, magnetic susceptibility, UV-vis and thermogravimetry-differential thermal analysis (TGA-DTA). From the magnetic moment and UV-vis spectra data, it is found that the geometrical structures of these complexes are octahedral.
Keywords: metal complexes; spectroscopy; transition metal compounds